Theoretical Bases of Professional Training of the Future Primary School Teachers in the Countries of Eastern Europe - BinytskaКateryna (Pedagogical Discourse, 2016)
In the article the author carried out general analysis of the theoretical bases of professional training of the future primary school teachers in the countries of Eastern Europe. The importance of studying the experience of training of the future primary school teachers of the countries of Eastern Europe that will reveal new possibilities for improvement of pedagogical education of Ukraine in terms of its adaptation to the requirements of the general European education space has been mentioned. In article the main aspects of scientific research of domestic comparativists about the professional preparation of the future primary school teachers in the countries of Eastern Europe have been cleared out. Taking into consideration the common historical, ethnic, political, religious, cultural conditions of development of some regions of Ukraine bordering with the countries of Eastern Europe – members of EU, of special interest, first of all, is the experience of the new EU members – Eastern European countries (Poland, Romania, Slovakia, Czech Republic, Hungary) in relation to the preparation of the future primary school teachers, since in the recent past, the primary education system of these countries and Ukraine had a lot in common. Based on the analysis of modern researches and publications on the problem of professional training of the future primary school teachers in Eastern European countries, the author mentions the need to establish a universal and at the same time effective for different countries, the model of the modern primary school teacher. The contradictions between the requirement of internationalization of education and the lack of generalized information about the experience of training primary school teachers in Eastern Europe. Key words: professional training, future primary school teachers, countries of Eastern Europe.